Midazolam is effective to reduce cortical network activity in organotypic cultures during severe cholinergic overstimulation with soman. (November 2018) - Drexler, Berthold; Seeger, Thomas; Worek, Franz; Thiermann, Horst; Antkowiak, Bernd; Grasshoff, Christian
Highlights: Organophosphorous (OP) intoxication was induced in cortical slice cultures. Neuronal activity is elevated during OP intoxication in cortical cultures. Midazolam attenuates neocortical activity even during elevated cholinergic tone. Results support the benefit of using midazolam in the treatment of OP intoxication. Abstract: Intoxication with organophosphorus compounds can result in life-threatening organ dysfunction and refractory seizures. Sedation or hypnosis is essential to facilitate mechanical ventilation and control seizure activity. The range of indications for midazolam includes both hypnosis and seizure control. Since benzodiazepines cause sedation and hypnosis by dampening neuronal activity of the cerebral cortex, we investigated the drug's effect on action potential firing of cortical neurons in brain slices. Extensive cholinergic overstimulation was induced by increasing acetylcholine levels and simultaneously treating the slices with soman to block acetylcholinesterase activity. At control conditions midazolam reduced discharge rates (median/95% confidence interval) from 8.8 (7.0–10.5) Hz (in the absence of midazolam) to 2.2 (1.4–2.9) Hz (10 μM midazolam) and 1.6 (0.9–2.2) Hz (20 μM midazolam). Without midazolam, cholinergic overstimulation significantly enhanced neuronal activity to 13.1 (11.0–15.2) Hz. Midazolam attenuated firing rates during cholinergic overstimulation to 6.5 (4.8–8.2) Hz (10 μM midazolam) and 4.1 (3.3–6.0) Hz (20 μM midazolam), respectively. Thus, high cholinergic tone attenuated the drug's efficacy only moderately. These results suggest that midazolam is worth being tested as a promising drug to induce sedation and hypnosis in patients suffering from severe organophosphorous intoxication.